Foraging Behavior and Pollination Efficiency of Apis mellifera L. on the Oil Tree Peony ‘Feng Dan’ (Paeonia ostii T. Hong et J.X. Zhang) - He, Chunling; Zhang, Kaiyue; Hou, Xiaogai; Han, Dongbo; Wang, Shuaibing (Insects (Basel, Switzerland), 2019)
To solve the issue of insufficient pollinating of insects for the oil tree peony ‘Feng Dan’ (Paeonia ostii T. Hong et J.X. Zhang) and improve its seed set and yield, we conducted observations from 2017 to 2018 to investigate the relationship between honey bee (Apis mellifera L.) foraging behavior and diurnal activity. We compared the single-fruit seed set ratio among three flower types on the same plants of the oil tree peony, which flowered simultaneously, in three pollination areas (bee pollination, natural field pollination, and controlled pollination by pollinators) and in a net room under self-pollination, wind pollination and bee pollination. Apis mellifera exhibited short single visitations, long visitations to a single flower and repeated visits to flowers of the oil tree peony. The number of flower visits of A. mellifera was significantly and positively yet weakly correlated with the number of stigma visits (2017: r = 0.045, p < 0.05; 2018: r = 0.195, p < 0.01). The seed set of oil tree peony follicles in the A. mellifera pollination area was significantly higher than that in the natural pollination field area and the control net rooms. On the same oil tree peony plant with synchronous flowering, the percent seed set of follicles pollinated by A. mellifera at a high density was significantly higher than that resulting from wind pollination and self-pollination.